Thermal stability and kinetics of thermal degradation of PMVS/SiO2/GO‐C12‐hep composites. Issue 1 (20th March 2013) - Qiu, Huating; He, Chengai; Zhou, Lianjie; Shao, Hongyun; Fan, Hongjie; Mo, Hong; Zhang, Jun; Zhou, Ninglin; Shen, Jian
Abstract In this study, a series of the PMVS/SiO2/GO‐C12‐hep (polymethylvinyl siloxane, PMVS) nanocomposites of varying fillers concentration were fabricated employing blending technique. Retained tensile tests showed that tensile strength of PMVS/SiO2/GO‐C12‐hep nanocomposites improved with increasing of GO‐C12‐hep content from 0 to 0.5 wt %, but it decreased when the GO‐C12‐hep content was up to 0.8 wt %. SEM results showed that GO/C12‐hep had been dispersed into PMVS matrix, and the interfacial consistency property was very well between GO‐C12‐hep and PMVS. The degradation mechanism was also analyzed. The thermal stability and the degradation kinetics of nanocomposites had been evaluated using thermo‐gravimetric analysis (TGA) at different heating rates in flowing nitrogen. TGA curves revealed that PMVS/SiO2/GO‐C12‐hep exhibited relatively better thermal stability than PMVS/SiO2, and the degradation temperatures of PMVS/SiO2/GO‐C12‐hep increased with GO‐C12‐hep increase. The apparent activation energies (Ea) were estimated with the Flynn–Wall–Ozawa method (FWO method). The Ea of PMVS/SiO2/GO‐C12‐hep nanocomposites had relevance to their content of GO‐C12‐hep. © 2013 Wiley Periodicals, Inc. J. Appl. Polym. Sci., 2013